PENILAIAN DAMPAK KEBAKARAN PADA TEGAKAN AKASIA DI BKPH PARUNG PANJANG KPH BOGOR, PERUM PERHUTANI UNIT III JAWA BARAT DAN BANTEN Fire Severity Assessment on Akasia stand at BKPH Parung Panjang KPH Bogor, Perum Perhutani III West Java and Banten - Lailan Syaufina; Vera Linda Purba (Jurnal Silvikultur Tropika, 2017)
Forest fire is one of the problem in forest management. The objectives of the study was to measure the forest fire severity based on soil physical and chemical properties. The forest fire effects were assessed using fire severity method and forest health monitoring plot. The study indicated that the burned areas at BKPH Parung Panjang after two years included in low fire severity. The site properties and growth performance analysis showed that the fire has only affected on pH, Mg and tree diameter significantly, whereas the other parameters such as bulk density, P, N, Na, K, Ca and height were not significantly affected. In addition, both burned and unburned areas are classified as in health condition.Key words : fire severity, forest health monitoring, growth performance, site properties